2009
DOI: 10.1038/npp.2009.180
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in GRIK4, HTR2A, and FKBP5 Show Interactive Effects in Predicting Remission to Antidepressant Treatment

Abstract: Single-nucleotide polymorphisms (SNPs) in the FKBP5, GRIK4, and HTR2A genes have been shown to be associated with response to citalopram treatment in the STAR*D sample, but only associations with FKBP5 have so far been tested in the Munich Antidepressant Response Signature (MARS) project. Response and remission of depressive symptoms after 5 weeks of antidepressant treatment were tested against 82 GRIK4 and 37 HTR2A SNPs. Association analysis was conducted in about 300 depressed patients from the MARS project,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(105 citation statements)
references
References 84 publications
7
96
1
1
Order By: Relevance
“…SSRIs) treatment response accounts for genetic factors, progress in uncovering the particular genetic polymorphisms has been slow [112]. As described in Table 1, candidate gene studies have pointed to a number of genes and SNPs that may influence antidepressant treatment outcomes [6, 7, 8-10, 26, 27, 54], including polymorphisms within the COMT [8,30], HTR2A [54,86,121], HTR1A [26], CNR1 [26], SLC6A4 [9], NPY [6], MAOA [27,30], IL1B [7,30], GRIK4 [64], BDNF [30,86], GNB3 [30], FKBP5 [86], CYP2D6 [31,121], CYP2C19 [31,121], and ABCB1 [12,86] genes (Table 1). For example, a negative influence of a higher activity COMT 158 val/val genotype on antidepressant treatment response was shown [].…”
Section: Ssris Treatment For Major Depressive Disordermentioning
confidence: 99%
“…SSRIs) treatment response accounts for genetic factors, progress in uncovering the particular genetic polymorphisms has been slow [112]. As described in Table 1, candidate gene studies have pointed to a number of genes and SNPs that may influence antidepressant treatment outcomes [6, 7, 8-10, 26, 27, 54], including polymorphisms within the COMT [8,30], HTR2A [54,86,121], HTR1A [26], CNR1 [26], SLC6A4 [9], NPY [6], MAOA [27,30], IL1B [7,30], GRIK4 [64], BDNF [30,86], GNB3 [30], FKBP5 [86], CYP2D6 [31,121], CYP2C19 [31,121], and ABCB1 [12,86] genes (Table 1). For example, a negative influence of a higher activity COMT 158 val/val genotype on antidepressant treatment response was shown [].…”
Section: Ssris Treatment For Major Depressive Disordermentioning
confidence: 99%
“…This first report was replicated in 2 subsequent studies; 261,431 however, a more recent study showed controversial results. 432 Furthermore, genes encoding for GRIK2, GRIA1, GRIA3 and GRIN3A receptors have been recently investigated in relation with response to sexual side effects from antidepressant treatment. 431,433,434 However, the study of the relation between genetic variants in the glutamate system and antidepressant response is a promising topic in pharmacogenetics.…”
Section: Glutamatergic Receptorsmentioning
confidence: 99%
“…Furthermore, a study has also found an independent and interactive involvement of FKBP5 (as well as GRIK4 and HTR2A) in antidepressant treatment response (Horstmann et al, 2010), emphasizing the potential importance for treatment in the study of this gene.…”
Section: Introductionmentioning
confidence: 99%